2007
DOI: 10.4319/lo.2007.52.2.0798
|View full text |Cite
|
Sign up to set email alerts
|

Release of dissolved organic matter by coastal diatoms

Abstract: Dissolved organic matter (DOM) production was examined in axenic batch cultures of five coastal diatom species. For Chaetoceros decipiens, dissolved organic carbon (DOC) accumulated beginning in late exponential growth as a result of increased cell density. For Cylindrotheca closterium, DOC actually decreased in late exponential growth and reached zero by the end of the experiment. This coincided with continued particulate organic carbon (POC) production and a threefold increase in the per-cell concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 38 publications
8
75
0
Order By: Relevance
“…It is assumed that the accumulation of DOM in phytoplankton cultures indicates the uncoupling of growth and photosynthesis. This is supported by the observation that the greatest release of DOM occurs during the transition between different phases of phytoplankton growth (Granum et al 2002;Wetz & Wheeler, 2007), which was explained by Williams (1990) as a 'temporary loss of control' of the organic matter pools within the cell as growth rate slows down. It is rarely considered that other processes, such as phytoplankton cell death resulting in lysis (Franklin et al, 2006), may also affect the release of DOM in batch cultures.…”
Section: Overflow Hypothesissupporting
confidence: 61%
See 1 more Smart Citation
“…It is assumed that the accumulation of DOM in phytoplankton cultures indicates the uncoupling of growth and photosynthesis. This is supported by the observation that the greatest release of DOM occurs during the transition between different phases of phytoplankton growth (Granum et al 2002;Wetz & Wheeler, 2007), which was explained by Williams (1990) as a 'temporary loss of control' of the organic matter pools within the cell as growth rate slows down. It is rarely considered that other processes, such as phytoplankton cell death resulting in lysis (Franklin et al, 2006), may also affect the release of DOM in batch cultures.…”
Section: Overflow Hypothesissupporting
confidence: 61%
“…Nagata concluded that mean PER in cultures is 5% (range 2-10%), with higher rates in stressed cultures (nutrient limitation or suboptimal conditions of light and temperature) or when cells were in the stationary and senescent stages of growth. Wetz & Wheeler (2007) also found PER rates of approximately 5% in batch cultures of four coastal diatom species: Cylindrotheca closterium, Odontella longicruris, Bellerochea sp., and Skeletonema sp. However, PER for Chaetoceros decipiens was higher, at 21%.…”
Section: Production Rates Of Dom By Phytoplanktonmentioning
confidence: 99%
“…Cell normalized production of PO 14 C was on average ∌ 0.33 pmol C cell −1 d −1 and well within the range of published values (0.12-0.64 pmol C cell −1 d −1 ; Biddanda and Benner, 1997;Borchard and Engel, 2012). The partitioning of organic carbon between dissolved and particulate pool was shown earlier to be highly influenced by environmental conditions such as light, temperature and nutrient supply (Myklestad and Haug, 1972;Zlotnik and Dubinsky, 1989;Staats et al, 2000;Wetz and Wheeler, 2007). Nutrient depletion, however, seems to be the major factor leading to excess DOC excretion from algae cells to the surrounding environment and was reported from a variety of field and lab experiments (Fogg, 1983;Wood and VanValen, 1990;Smith and Underwood, 2000;Lopez Sandoval, 2010.…”
Section: Particulate and Dissolved Primary Productionsupporting
confidence: 57%
“…Nevertheless, sea ice algae are known to exude high amounts of EPS [12], which is believed to play an important role in cryoprotection in microorganisms [14]. DOC release is also related to the state and age of the culture, and can exceed values measured in the field [54]. Hence, high levels of DOC release can be anticipated in cultured sea ice algae, growing in temperatures close to the freezing point of seawater [13].…”
Section: Discussionmentioning
confidence: 99%